Beyond litigation: Policy work within cause lawyering organizations. Issue 2 (19th May 2022) - Trowbridge, David L.
Abstract: This article investigates why cause lawyering organizations choose policy work and how policy agendas are set. Interviews and documents from eight legal organizations in the LGBTQ movement reveal that policy work expands the scope of conflict, giving organizations not only more opportunities to act, but potentially providing greater autonomy to lawyers by allowing them to build their own opportunities. Furthermore, policy agendas are not simply tied to litigation and resources. Organizations balance perceptions of opportunity and need with resource availability. These perceptions are often informed by collaborations with state and local organizations, facilitating communication between groups, organizers, and activists at different vantage points. Thus, the nature of a legal organization's multidimensional strategy, which expands opportunities to reach their goals, may be shaping what those goals are. These findings contribute to our understanding of cause lawyering tactics and agendas.